2017
DOI: 10.1039/c6tb02329k
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic activity and angiogenesis of a SrTiO3 nano-gridding structure on titanium surface

Abstract: Dual effect of alveolate double-layered SrTiO3 nano-gridding based on Ti substrate: osteogenic activity and angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Surface modification of titanium can significantly enhance the osteogenesis and antibacterial efficacy [35][36][37][38]. In this study, we fabricated a novel Zn-incorporated TiO 2 coating by MAO and subsequent hydrothermal treatment producing micro-nano topography on an SLM surface.…”
Section: Discussionmentioning
confidence: 99%
“…Surface modification of titanium can significantly enhance the osteogenesis and antibacterial efficacy [35][36][37][38]. In this study, we fabricated a novel Zn-incorporated TiO 2 coating by MAO and subsequent hydrothermal treatment producing micro-nano topography on an SLM surface.…”
Section: Discussionmentioning
confidence: 99%
“…Titanium‐based alloys with strontium incorporated on their surface yielded similar results. [ 16,131,132 ] The studies reported improved adhesive, migration, and tube formation properties in vitro, suggesting likely enhanced vessel formation in vivo.…”
Section: Interaction Of Endothelial Cells With Inorganic Angiogenic Agentsmentioning
confidence: 99%
“…To develop such a functional implant, surface modification is an effective approach. Recently, much research efforts on Ti surface modification, such as topographical modification and immobilization of bioactive molecules, have been carried out to enhance the osseointegration and antibacterial properties of the Ti materials . In general, Ti based implant materials with nanorod topologic structure exhibit inherent surface advantages thanks to their high surface area, controllable dimensions, and universal drug delivery capacity .…”
Section: Introductionmentioning
confidence: 99%